2021
DOI: 10.1002/cam4.4025
|View full text |Cite
|
Sign up to set email alerts
|

Definitive concurrent chemoradiotherapy with paclitaxel plus carboplatin is superior to cisplatin plus 5‐fluorouracil in patients with inoperable esophageal squamous cell carcinoma using retrospective, real‐world evidence

Abstract: Background The optimal definitive chemotherapy regimen during concurrent chemoradiotherapy (CRT) for patients with advanced esophageal squamous cell carcinoma (ESCC) remains unclear because of conflicting evidence. This study aimed to compare the effectiveness of taxane‐based chemotherapy with that of conventional cisplatin plus 5‐fluorouracil (PF) as the chemotherapy regimen in definitive CRT for ESCC. Patients and Methods This retrospective study included patients with ESCC who received paclitaxel plus carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
(91 reference statements)
0
6
0
Order By: Relevance
“…Through preliminary inspection, a total of 1300 relevant studies were obtained, including 1298 which met the inclusion criteria and 2 similar reading articles. After further screening, 34 articles were obtained for further evaluation [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Among these studies, the chemotherapy regimen of one and the study objects of two did not meet the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through preliminary inspection, a total of 1300 relevant studies were obtained, including 1298 which met the inclusion criteria and 2 similar reading articles. After further screening, 34 articles were obtained for further evaluation [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Among these studies, the chemotherapy regimen of one and the study objects of two did not meet the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Among these studies, the chemotherapy regimen of one and the study objects of two did not meet the inclusion criteria. Finally, a total of 31 articles involving 3432 participants were included [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. The detailed retrieval process of this review is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…A retrospective study conducted by Hsieh JC et al also showed a DCR of 71.1% after chemotherapy with TP regimen, significantly higher than 51.4% for PF ( p = 0.016); therefore, for patients with advanced ESCC, the combination chemotherapy regimen of cisplatin plus paclitaxel may be more suitable. 19 In the univariate regression analysis, we excluded the impact of ICIs types on the effectiveness of patients in the experimental group. Therefore, the difference in PFS and OS of patients in the experimental group is related to the chemotherapy regimen combined with ICIs, ICIs plus TP can benefit patients more than ICIs plus PF regimen.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, patients underwent neoadjuvant chemotherapy according to the results of the JCOG9907 trial [ 14 ]. However, the regimen used in our study was based on docetaxel instead of 5-fluorouracil, as taxane-based neoadjuvant chemotherapy might be associated with better response rates and more favourable survival in patients with advanced ESCC [ 15 17 ]. Klevebro et al found that nCRT resulted in a higher histological complete response rate and higher R0 resection rate than nCT [ 2 ].…”
Section: Discussionmentioning
confidence: 99%